Landslide Accumulation Ice-Snow Melting for Thermo-Hydromechanical Coupling and Numerical Simulation - Xiong, Tongqiang; Li, Jianlin; Wang, Lehua; Deng, Huafeng; Xu, Xiaoliang (Advances in Civil Engineering, 2021)
In this paper, we discussed the phase change coupling algorithm of accumulation bank slope under the action of ice-snow melting. We described the effect of temperature gradient on the water migration of soil. We simplified the stress balance, continuity, and energy equation in the coupled model. We discussed the variation law of temperature, seepage, and stress (deformation) field under different conditions of ice-snow melting on the bank slope of the accumulation body. Based on the three-field coupling energy balance equation of ice-snow melting with phase change, the simplified algorithm of three-field coupling is obtained. The simplified algorithm is applied to the coupling model of ice-snow thawing on indoor accumulation bank slope. We established a practical numerical model for the coupling analysis of temperature, seepage, and stress field. We established the coupled control differential equation of three fields. We investigated the three-dimensional numerical simulation of stress, displacement, plastic deformation, and other indicators. The results show that the numerical simulation results are in good agreement with the monitoring results. It is expected that the research results can more truly simulate the actual characteristics of ice and snow melting water on the bank slope of the Three Gorges Reservoir and provide reference for the prevention and prediction of extreme snow and ice disasters in the Three Gorges Reservoir area.